SISTEM INFORMASI TRACKING PENGIRIMAN PAKET BARANG SECARA ONLINE BERBASIS WEB (STUDI KASUS: PT. GUNUNG HARTA TABANAN - BALI) - Faiqotul Aminah (IZZI: Jurnal Ekonomi Islam, 2021)
PT. Gunung Harta Tabanan - Bali is a company engaged in transportation services that were founded by Mr. I WAYAN SUTIKA in 1993. At that time this company only had a means of inter-city transportation within the province (AKDP) serving the Denpasar - Gilimanuk route only. Then from year to year, there has been a development, namely the addition of 125 buses and the addition of 10 boxcars which are used for the delivery of express packages. The problems faced by PT. Gunung Harta Tabanan - Bali is the occurrence of delays and shortages in the number of goods sent. This study aims to produce a web-based online package delivery tracking information system that is more sophisticated and better than the previous system. The system development technique used in this research is the waterfall model development technique and the programs used in making this application are WEB programming along with PHP and MySQL. The result of this research is a web-based online package delivery tracking information system that is proven to provide benefits and fulfill the needs analysis aspects for customers because they no longer need to go directly to the PT. Gunung Harta to carry the package of goods to be sent. Besides, customers can also monitor the package status of the goods they are sending.